1994
DOI: 10.1016/0035-9203(94)90200-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of DDT spraying and bed nets impregnated with pyrethroid insecticide on the incidence of Japanese encephalitis virus infection

Abstract: A retrospective investigation was conducted to evaluate the effectiveness of DDT residual indoor spraying and bed nets impregnated with pyrethroid insecticide for Japanese encephalitis control in southern Henan province, China. DDT residual indoor spraying had no effect on the incidence of Japanese encephalitis, but it was greatly reduced after the introduction of pyrethroid-impregnated bed nets. Only a small effect on outdoor biting densities of Culex tritaeniorhyncus was found, although the number of mosquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…A previous study in China suggested that the use of pyrethroid-impregnated bed nets significantly reduced the JE incidence in humans in the intervention group compared with the non-intervention group. 28 Bed nets impregnated with pyrethroid insecticide greatly decreased the risk of JEV infection among children under 10 years old, as noted in another study carried out in China.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…A previous study in China suggested that the use of pyrethroid-impregnated bed nets significantly reduced the JE incidence in humans in the intervention group compared with the non-intervention group. 28 Bed nets impregnated with pyrethroid insecticide greatly decreased the risk of JEV infection among children under 10 years old, as noted in another study carried out in China.…”
mentioning
confidence: 77%
“…This finding is consistent with the view that pyrethroid-impregnated bed nets have only a small effect on outdoor biting densities of mosquitos. 28 Immigration of younger mosquitoes from outside the treated area (pigsty and house) might be another reason for the lack of significant decrease in vector population during the pre-and post-intervention periods. This study reveals that, despite the high preponderance of potential vectors in study localities in the post-intervention period, an encouraging line of defense against circulation of JEV in community through the use of ITMN can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted in central China, bed netting without chemical impregnation did not protect children against JE, but pyrethroid treatment of bed nets in late May or June conferred protective efficacies of 28-48%. 40,41 Insecticides for bed net impregnation are not widely available for use in northern Vietnam. It has been well established that the mosquito vector of JE, Cx.…”
Section: Discussionmentioning
confidence: 99%
“…tritaeniorhynchus, tends to bite much more frequently outdoors than indoors, which would explain why such household protection measures as bed netting, window coverings or DDT residual indoor spraying are likely to have only limited impact. [40][41][42] Since indoor protection measures are marginally effective, and outdoor application of insecticide is not feasible because of the vast breeding reservoirs of Cx. tritaeniorhynchus, vaccination is the most promising means of reducing the incidence of JE in Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Assam, India, a sharp reduction in JE sero-conversion rates in people and pigs was achieved when insecticide treated nets were used in both people and pigs [24]. Similarly, a population based case-control study in China found that use of insecticide treated nets was associated with significant reduction in JE cases [25].There were significant differences in use of various mosquito control techniques in different districts in our study, often related to socio-economic factors. For example, the use of window screen was higher in Rupandehi because the pig farmers more often had permanent houses with windows compared to pig farmers of Kathmandu, Morang and Kapilvastu districts who often lived in homes without windows.…”
Section: Discussionmentioning
confidence: 99%